Necesidad de regular la protección jurídica del non nato en el ecuador.- proyecto de reforma al código civil - Mullo Avemañay, Moisés (2015)
Whithin contemporany problems is the star of human live and the protection of the unborn. Indeed, there have been several doctrinal and theological positions including, from those clasicc Roman considering the unborn as a mother and as a being vísceras potential suspends vesting until the moment of birth status is verified. Also in acculturation theories that seek to see the acceptance of the mother as a condition for the beginning of human life, to the position that views live as a continuum in which the vital process never stopped but only continues into a new being in the time of syngamy. Indeed, the law has to set its rules on certain specific and well –made, and not on mere assumptions or approximate concepts, so as in general has historically taken into account, as a starting point, the birth, while recognizing the previous life, which has also protecteg, but differently. Currently, however, the way in which the law protected the unborn has been overwhelmed by current considerations to understand the unborn as a subject of individual rights from the moment of conception, pending when it takes only determine this. In short, the law has always protected as a subject of right to born as a subject worthy of protection to the unborn, yet today is considered, especially in international human rights conventions that the unborn child is a subject of rights from the momento of conception, which subtantially affects the legal system form. These different positions have led in turn to the legal frameword in a series of standards, even contradictory, as to when to consider the beginning of human life and, therefore, when they occur the unborn is considered subjective rights holder. In Ecuador several existing rules in various legal bodies, which is considered the unborn in various ways, from a full subject of rights from conception to as subject worthy of legal protection are opposed. Even, there are laws that run counter to norms of international law that are clearly unconstitutional